2000
DOI: 10.1038/sj.ejcn.1601083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of plant sterol ester and plant stanol ester-enriched margarines in lowering serum cholesterol concentrations in hypercholesterolaemic subjects on a low-fat diet

Abstract: Objective: To investigate cholesterol-lowering effects of stanol ester (STAEST) and sterol ester (STEEST)-enriched margarines as part of a low-fat diet. Design: According to a Latin square model randomized double-blind repeated measures design with three test margarines and three periods. Setting: Outpatient clinical trial with free-living subjects. Subjects: Thirty-four hypercholesterolaemic subjects completed the study. Interventions: Subjects consumed three rapeseed oil-based test margarines (STAEST, STEEST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
3
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(158 citation statements)
references
References 34 publications
12
137
3
6
Order By: Relevance
“…Efficacy may depend on many different factors like intake level (Hendriks et al, 1999;Hallikainen et al, 2000a), background diet (Hallikainen et al, 2000b;Denke, 1995), composition of the sterol mixture (Jones et al, 2000;Sierksma et al, 1999) and specific characteristics of the subjects studied Tammi et al, 2000;Vuorio et al, 2000), like genetic background, compliance and eating moment. Mietinen et al (1995) reported a slightly higher efficacy, most likely due to the larger intake of plant stanols as compared with the plant sterol intake in the trial reported here (2.6 g stanols vs 1.6 g sterols per day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy may depend on many different factors like intake level (Hendriks et al, 1999;Hallikainen et al, 2000a), background diet (Hallikainen et al, 2000b;Denke, 1995), composition of the sterol mixture (Jones et al, 2000;Sierksma et al, 1999) and specific characteristics of the subjects studied Tammi et al, 2000;Vuorio et al, 2000), like genetic background, compliance and eating moment. Mietinen et al (1995) reported a slightly higher efficacy, most likely due to the larger intake of plant stanols as compared with the plant sterol intake in the trial reported here (2.6 g stanols vs 1.6 g sterols per day).…”
Section: Discussionmentioning
confidence: 99%
“…Four doubleblind placebo-controlled studies directly compared the efficacy of plant sterols and stanols (Weststrate & Meijer, 1998;Hallikainen et al, 2000b;Jones et al, 2000;Normen et al, 2000). These short-term human trials, either dietary controlled or in free-living conditions, showed a similar (Weststrate & Meijer, 1998;Hallikainen et al, 2000b;Normen et al, 2000) or a better (Jones et al, 2000) blood cholesterol lowering efficacy for plant sterol esters-enriched spreads compared with spreads enriched with plant stanol esters.…”
Section: Discussionmentioning
confidence: 99%
“…The target cDNA templates from one hamster were amplified with the degenerated primers by PCR (Perkin Elmer Applied Biosystems, Wellesley, USA). After separation from the templates by electrophoresis on acrylamide gel, the PCR products were purified and cloned using plasmid pCR 4 -TOPO (Invitrogen, Ontario, Canada). Recombinant plasmids were purified using a plasmid mini kit (Qiagen, Ontario, Canada).…”
Section: Hamster Abcg5 and Abcg8 Sequencesmentioning
confidence: 99%
“…When the absorption of cholesterol decreases, the synthesis of cholesterol in the liver increases, thus enhancing cholesterol turnover (Gylling et al, 1999). Several studies have shown that 2-3 g of plant stanols per day reduces total and low-density lipoprotein cholesterol (LDL-C) concentrations without changing highdensity lipoprotein cholesterol (HDL-C) and triglyceride (TG) concentrations Hallikainen et al, 2000a;Nestel et al, 2001;Mensink et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, the cholesterol-lowering effect of plant stanol ester has been studied with plant stanols incorporated in an ordinary or low-fat margarine (Gylling and Miettinen, 1994;Gylling et al, 1995Gylling et al, , 1997Miettinen et al, 1995;Hallikainen and Uusitupa, 1999;Hallikainen et al, 2000aHallikainen et al, , b, 2002Tammi et al, 2002) or mayonnaise (Vanhanen et al, 1993;Miettinen and Vanhanen, 1994). Mensink et al (2002) also reported that a yoghurt enriched with 3 g/day of plant stanols reduced LDL cholesterol significantly.…”
Section: Introductionmentioning
confidence: 99%